Strategies for overcoming conflict among future leaders of different religious orientations at a period of society digitalisation - I. K. Shcherbakova; I. E. Sokolovskaya (Вестник университета)
The article deals with historical, legal, sociological, psychological and other aspects of conflict resolution in society and social groups. The results of a survey of undergraduate students of the State University of Management are presented. On the basis of the study, strategies for resolving conflict situations among future leaders of various religious orientations, and means of resolving interpersonal and intergroup conflicts, were identified. Using methods of expert analysis, by comparing respondents’ opinions with those of researchers, it is concluded that digital training should be introduced to acquire online knowledge on preventing and dealing with controversial situations. In this way, Russia’s future leaders could be trained in appropriate reactions in conflict educational situations, learn how to apply different styles and strategies of communication, and to identify conflictogens at the first and second stages of conflict development to promptly transfer such situations to a peaceful course. The practical significance of the study is in the implementation of the results to test students for the level of emotional intelligence, to improve their competencies, and to resolve conflicts in different ethnic environments.